2021
DOI: 10.3389/fphar.2021.695687
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Na+/Ca2+ Exchanger Inhibitor CGP37157 Preserves Muscle Structure and Function to Increase Lifespan and Healthspan in Caenorhabditis elegans

Abstract: We have reported recently that the mitochondrial Na+/Ca2+ exchanger inhibitor CGP37157 extends lifespan in Caenorhabditis elegans by a mechanism involving mitochondria, the TOR pathway and the insulin/IGF1 pathway. Here we show that CGP37157 significantly improved the evolution with age of the sarcomeric regular structure, delaying development of sarcopenia in C. elegans body wall muscle and increasing the average and maximum speed of the worms. Similarly, CGP37157 favored the maintenance of a regular mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Previous research revealed that mitochondrial Ca 2+ is essential for the regulation of mitochondrial function and ATP generation ( García-Casas et al, 2021 ). To check whether the decrease in ATP results from the decline in mitochondrial Ca 2+ , the mitochondrial Ca 2+ level in muscle cells was analyzed by monitoring the intensity of GCaMP, a genetic fluorescent mitochondrial calcium indicator.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research revealed that mitochondrial Ca 2+ is essential for the regulation of mitochondrial function and ATP generation ( García-Casas et al, 2021 ). To check whether the decrease in ATP results from the decline in mitochondrial Ca 2+ , the mitochondrial Ca 2+ level in muscle cells was analyzed by monitoring the intensity of GCaMP, a genetic fluorescent mitochondrial calcium indicator.…”
Section: Resultsmentioning
confidence: 99%
“…In our laboratory we have recently found that modulation of some systems involved in intracellular Ca 2+ homeostasis is capable of extending lifespan and improving functional parameters representative of better health in C. elegans nematodes ( García-Casas et al, 2018 ; 2019 ; 2021a ; 2021b ). One of these systems is the ER Ca 2+ pump or SERCA, whose partial inhibition, either with inhibitors or with RNAi, produced a significant increase in the lifespan in wild type worms ( García-Casas et al, 2018 ; 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…The two most broadly used Ca 2+ sensors in C. elegans are GCaMPs and FRET-based cameleons, the most frequently expressed in neurons or muscular cells [44,[212][213][214], alone or under the optogenetic manipulation of neuronal activity [215]. Although the majority of the studies in C. elegans have been performed using untargeted probes expressed in the cytosol, relevant examples of Ca 2+ sensors expressed in organelles exist, e.g., mito-chondria [216][217][218]. Recently, advanced approaches allowed whole-brain Ca 2+ imaging, in which about 100 neurons were simultaneously monitored in moving worms [219,220].…”
Section: Ca 2+ Imaging In Caenorhabditis Elegansmentioning
confidence: 99%